Innovative and anti-corruption technologies - Soroka, E. O.; Pererva, P. G. (My University, 2023)
It is confirmed that ensuring the economic security of an industrial enterprise is not the prerogative of any state or corporate department or service. This should be supported by the entire system of state bodies, all links and management structures of the enterprise's industry.
Keywords: corruption; legislation; moral attitudes; bribes